Internal resistance and polarization dynamics of lithium-ion batteries upon internal shorting. (15th February 2018) - Noelle, Daniel J.; Wang, Meng; Le, Anh V.; Shi, Yang; Qiao, Yu
Graphical abstract: Highlights: Understanding resistive dynamics informs thermal runaway mitigation strategies. Internal resistance at high discharge rates is dynamic and nonlinear. Electrical resistances dictate short circuit current in crucial first seconds. Rapid polarization depletes lithium-ion presence in electrolyte of cathode region. Ionic resistances throttle short circuit heating rates upon cell polarization. Abstract: Internal resistance and temperature measurements are made for LIR2450 format LiCoO2 /graphite 120 mA h coin cells upon abusive discharge conditions. The dynamic contributions of electrical and ionic resistances to joule heat generation are investigated in the earliest stages of battery failure. It is shown that while ohmic, primarily electrical resistances initially dictate the joule heating rates, polarization, primarily ionic resistances become dominant as time progresses. Ionic conductivity and resistance of LiPF6 salt in ethylene carbonate/ethyl methyl carbonate solvent are examined through concurrent concentration, viscosity, and temperature measurements to elucidate the intricacies of electrolyte polarization. Comparative analysis suggests that upon polarization at high discharge rates, resistance is concentrated in the electrolyte within the cathode region due to rapid depletion of lithium-ions available to facilitate charge transfer. Expected consequences are corroborated in external shorting and nail penetration experiments. The findings are used to predict how a cell would respond if electrical or ionic resistances are exacerbated upon shorting, so as to identify effective thermal runaway mitigation strategies.